Trends in Intelligent Robotics 15th Robot World Cup and Congress, FIRA 2010, Bangalore, India, September15-19, 2010, Proceedings - Vadakkepat, Prahlad; Kim, Jong-Hwan; Jesse, Norbert; Al Mamun, Abdullah; Kiong, Tan Kok; Baltes, Jacky; Anderson, John; Verner, Igor; Ahlgren, David (Communications in Computer and Information Science, 2010)
th This volume contains the papers selected for the 13 FIRA Robot World Congress, held at Amrita Vishwa Vidyapeetham Bangalore, India, September 15-17, 2010. The Federation of International Robot-soccer Association (FIRA - www.fira.net) is a non-profit organization that annually organizes robotic competitions and meetings around the globe. The robot soccer competitions started in 1996, and FIRA was est- lished on, June 5, 1997. The robot soccer competitions are aimed at promoting the spirit of science and technology to the younger generation. The congress is a forum to share ideas and future directions of technologies, and to enlarge the human networks in the robotics area. The objectives of the FIRA Cup and Congress are to explore the technical dev- opments and achievements in the field of robotics, and provide participants with a robot festival including technical presentations, robot soccer competitions, and exh- its under the theme "Where Theory and Practice Meet." FIRA India aims to propagate and popularize robotics and robotic competitions across India.